Writing all wrongs - Adams, Ellery (Adams, Ellery. Books by the bay mystery., 2015)
While attending the Coastal Carolina Crime Festival where Silas Black, a celebrity screenwriter and television producer is speaking, newlyweds Olivia and Chief Rawlings, along with the rest of the Bayside Book Writers, are faced with strange occurrences and a real-life murder.